Formulasi dan Evaluasi Sediaan Patch Ekstrak Getah Batang Pisang Ambon Sebagai Penyembuh Luka Sayat - Sukma; Nuralim, Bili (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Bananas are fruit that is easily obtained and high nutritional value. Ambon banana stem sap contains flavonoid compounds that are used to accelerate wound healing. The purpose of this study was to make a patch preparation from Ambon banana stem latex extract. Method: The type of research uses an experimental method by making several patch formulas containing Ambon banana stem latex extract with a concentration of 0%, 30%, 35%and 40%. And physical evaluation of the patch preparation includes organoleptic tests at temperatures (1º-4ºC), (25º-28ºC) and (40ºC), uniformity of weight, pH, thickness and fold resistance Result: The physical evaluation results show storage at temperatures (25º-28ºC) better and more stable, especially in organoleptic tests because they do not experience changes in shape, odor and color. The weighing uniformity test of all concentrations has an average uniformity of 0.07 and 0.08 grams. All stable formulas have a pH of 6 and in accordance with the requirements of the skin pH of 4.5-6.5. Patch thickness test concentration 0% 0.06 µm, concentration of 30%; 35 % 0.07 µm, and concentration of 40 % 0.07 µm. All concentrations meet the fold requirements ≥ 200 times the fold Conclusion Based on all physical evaluation tests conducted concentrations of 35 % and 40 % are the best and most stable preparations.